2016
DOI: 10.1016/j.cej.2016.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical regeneration of a graphite adsorbent loaded with Acid Violet 17 in a spouted bed reactor

Abstract: h i g h l i g h t sA two-phase reactor is a promising alternative to traditional three-phase reactor. The spouted bed region defined an interesting operating domain. Study of current density and the liquid flow rate on the system performance. A model is developed for the adsorption and electrochemical regeneration process. a b s t r a c tA novel spouted bed reactor is evaluated for water treatment by an adsorption and electrochemical regeneration process. The adsorbent is a bisulphate graphite intercalation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It has been widely reported that pollutants removal improves with increasing the current density (Lin and Peng 1996). Using higher current densities may reduce the treatment time to remove the COD and TOC from the wastewater, however, it will induce an increase of the cell potential (V CELL ) which results in increased energy consumption and decreased current efficiency (Liu et al 2016, Marcionilio et al 2016, Martinez-Huitle et al 2015, Yasri et al 2015. Anglada et al (2010) shows that in an electrochemical system for landfill leachate treatment by BDD anodic oxidation, an increase of the current density from 300 to 600 A m -2…”
Section: Energy Consumptionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been widely reported that pollutants removal improves with increasing the current density (Lin and Peng 1996). Using higher current densities may reduce the treatment time to remove the COD and TOC from the wastewater, however, it will induce an increase of the cell potential (V CELL ) which results in increased energy consumption and decreased current efficiency (Liu et al 2016, Marcionilio et al 2016, Martinez-Huitle et al 2015, Yasri et al 2015. Anglada et al (2010) shows that in an electrochemical system for landfill leachate treatment by BDD anodic oxidation, an increase of the current density from 300 to 600 A m -2…”
Section: Energy Consumptionmentioning
confidence: 99%
“…GAC can catalyze the decomposition of the electrochemically generated H 2 O 2 leading an increased generation of • OH and enhancing the performance of the 3D system (Lücking et al 1998, Zhou andLei 2006b). Oxidant species electrogenerated at the surface of GAC particles can react with the adsorbed pollutants and enable a partial regeneration of the bed material (Cañizares et al 2004, Liu et al 2016, Zhou and Lei 2006a.…”
Section: = − Equation 11mentioning
confidence: 99%
See 3 more Smart Citations